Are we exploring the potential role of specialized techniques in muscle hypertrophy? - Kassiano, W.; de Vasconcelos Costa, B. D.; Nunes, J. P.; Aguiar, A. F.; de Salles, B. F.; Silva Ribeiro, A. (International Journal of Sports Medicine, 2021)
Specialized resistance training techniques (e.g., drop-set, rest-pause) are commonly used by well-trained subjects for maximizing muscle hypertrophy. Most of these techniques were designed to allow a greater training volume (i.e., total repetitions×load), due to the supposition that it elicits greater muscle mass gains. However, many studies that compared the traditional resistance training configuration with specialized techniques seek to equalize the volume between groups, making it difficult to determine the inherent hypertrophic potential of these advanced strategies, as well as, this equalization restricts part of the practical extrapolation on these findings. In this scenario, the objectives of this manuscript were 1) to present the nuance of the evidence that deals with the effectiveness of these specialized resistance training techniques and — primarily — to 2) propose possible ways to explore the hypertrophic potential of such strategies with greater ecological validity without losing the methodological rigor of controlling possible intervening variables; and thus, contributing to increasing the applicability of the findings and improving the effectiveness of hypertrophy-oriented resistance training programs.